Active Rectifiers in the Electrical System of Aircraft - Bielokha, Halyna; Shevchenko, Ivan (2021 IEEE International Conference on Modern Electrical and Energy Systems (MEES), 2021)
This article features an overview of active three-phase rectifiers for autonomous power supply systems that include the electrical system of aircraft. Rectifiers are subject to strict current quality requirements according to the More Electric Aircraft (MEA) concept, which is the dominant trend in aircraft engineering. This article considers four alternate schemes of active rectifiers with a histeresis current control that are powered by a three-phase network with a frequency of 400 kHz. The results of modeling, harmonious composition of current and its compliance with quality standards are described in this article. The comparative characteristic of rectifiers was carried out as well.